2015
DOI: 10.1260/0144-5987.33.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Geology and Hydrocarbon Accumulation of the Large Ultra-Deep Rewapu Oilfield in Tarim Basin, China

Abstract: Over the past five years, oil and gas exploration to marine facies carbonate rock in China took on a fast-growing tendency, and a lot of large-scale oil and gas fields were discovered in succession. Particularly in the north of Tarim Basin, the large-scale Rewapu oil field was recently discovered in the Ordovician carbonate rock layer system with buried depth of 7,000 meters, manifesting that a significant potential of exploration exists in Tarim Basin's deep layer and ultra deep layer of Tarim basin. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The reservoirs of some high-yield gas wells are generally located near the transition zone between the dolomite and limestone of the Yingshan Formation (GL1, GC6, GC8, and GC9). Studies have suggested that the natural gas originated mainly from the Manjiaer sag (Zhu et al., 2015b) and entered the Yingshan reservoirs from bottom to top along faults. The period of natural gas accumulation was relatively late, mainly during the Yanshanian period (Wang et al., 2014a; Yun and Cao, 2014).…”
Section: Geological Settingmentioning
confidence: 99%
“…The reservoirs of some high-yield gas wells are generally located near the transition zone between the dolomite and limestone of the Yingshan Formation (GL1, GC6, GC8, and GC9). Studies have suggested that the natural gas originated mainly from the Manjiaer sag (Zhu et al., 2015b) and entered the Yingshan reservoirs from bottom to top along faults. The period of natural gas accumulation was relatively late, mainly during the Yanshanian period (Wang et al., 2014a; Yun and Cao, 2014).…”
Section: Geological Settingmentioning
confidence: 99%
“…The fact that large volumes of light crude oil have been extracted from the Tazhong (TZ) area within the Tarim Basin highlights the great potential for massive petroleum exploration from deep layers in this region (He et al, 2016;Wang et al, 2014). Zhu et al (2015) reported the newly discovered Rewapu oilfield in Tarim Basin, which was well preserved due to low geothermal stress and quick deep burial. Wang et al (2015) analyzed sulfur-containing compounds in Ha9 and ZS1C crude oils, identifying DBT (dibenzothiophene) series compounds in Ha9 crude oil and thiadiamondoids with 1-3 cages in ZS1C crude oil.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrocarbon resource of a basin is related to source rock, depositional, and tectonic structures and thermal maturation of the organic matter (Yang et al, 2014;Zhu et al, 2015). Contributions have been made by Demaison (1980), Dembicki et al (1983), Mishra and Cook (1992), Peters (1986), Singh and Singh (1998), and Teichmuller and Durand (1983).…”
Section: Introductionmentioning
confidence: 99%
“…With progress in the coalification, not only the rank changes, but there is also change in the chemical composition and properties of the macerals. Hydrocarbon resource of a basin is related to source rock, depositional, and tectonic structures and thermal maturation of the organic matter (Yang et al., 2014; Zhu et al., 2015). Contributions have been made by Demaison (1980), Dembicki et al.…”
Section: Introductionmentioning
confidence: 99%